2022
DOI: 10.1108/jed-08-2022-0136
|View full text |Cite
|
Sign up to set email alerts
|

The environment, social and governance (ESG) activities and profitability under COVID-19: evidence from the global banking sector

Abstract: PurposeThis study investigated the impacts of the environment, social and governance (ESG) and its components on global bank profitability considering the COVID-19 outbreak.Design/methodology/approachThis study used a system generalized method of moments (GMM) proposed by Arellano and Bover (1995) to investigate the relationship between ESG and bank profitability using an unbalanced sample of 487 banks from 51 countries from 2006 to 2021.FindingsThe findings generally found that ESG activities may reduce bank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 63 publications
3
9
0
4
Order By: Relevance
“…Since the early phase of the COVID-19 pandemic, a number of measures have been applied and practiced in attempts to restrain and contain the spread of the COVID-19 infection; these include social distancing, hand washing, face-mask wearing, border shutdowns, quarantine, and travel restrictions, among others [ [7] , [8] , [9] , [10] , [11] ]. As part of the ongoing measures to restrict the spread of the COVID-19 pandemic, vaccination played a crucial role in curbing and resolving the COVID-19 pandemic [ [12] , [13] , [14] ]. Thus, shortly after the outbreak of the disease was declared, there was an urgent call for COVID-19 vaccine research and development by the WHO [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the early phase of the COVID-19 pandemic, a number of measures have been applied and practiced in attempts to restrain and contain the spread of the COVID-19 infection; these include social distancing, hand washing, face-mask wearing, border shutdowns, quarantine, and travel restrictions, among others [ [7] , [8] , [9] , [10] , [11] ]. As part of the ongoing measures to restrict the spread of the COVID-19 pandemic, vaccination played a crucial role in curbing and resolving the COVID-19 pandemic [ [12] , [13] , [14] ]. Thus, shortly after the outbreak of the disease was declared, there was an urgent call for COVID-19 vaccine research and development by the WHO [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vietnam is considered as an appropriate nation to recruit the data and examine the perceived barriers on intentions to receive COVID-19 vaccines under the mediation and moderation mechanism of self-efficacy, attitude towards COVID-19 vaccines, and psychological distress because the rationales as follows. First, the success of addressing the COVID-19 spread in three first waves by applying 5K (Khẩu trang-mask-wearing, Khử khuẩn-disinfection, Khoảng cách-social distancing, Không tụ tập đông người-No garthering, and Khai báo y tế- health declaration) has been proved in this country [ 3 , 12 , 28 , 39 ]. Second, at the time of this conducted research, although the self-development of COVID-19 vaccines (Nanocovax) was conducing in Vietnam, almost all Vietnamese people still did not receive COVID-19 vaccines and waited for the sources of COVID-19 vaccines from international supports.…”
Section: Methodsmentioning
confidence: 99%
“…Psychological distress reflects the unpleasant emotional reactions to stress states, which are unmanaged and overwhelmed [ 27 ]. Almost all prior studies only considered psychological distress as the detrimental factor of life satisfaction and/or well-being [ 28 , 29 ], while neglecting the moderation effect of psychological distress. In this study, we suppose that psychological distress can serve as the moderator which may facilitate or weaken the impacts of self-efficacy, attitudes towards COVID-19 vaccines, and perceived clinical and access barriers on intentions to receive COVID-19 vaccines.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Christensen et al (2021) pointed out in their literature review that several studies confirm the positive and significant relationship between ESG activities and financial performance. Yuen et al (2022) observed that there is a U-shaped relationship between ESG and profitability, reflecting that ESG activities improve bank performance in the long term. Ersoy et al (2022) examined 176 US commercial banks and they show an inverted U-shaped relationship between market value and ESG.…”
Section: Profitabilitymentioning
confidence: 99%